Assessment of organ doses for CT patients based on x-ray attenuation using water equivalent diameter. (April 2021) - Abuhaimed, Abdullah; Martin, Colin J.
Abstract: Organ doses for patients having CT scans can be assessed using Monte Carlo simulations, but this would require significant computing power if carried out for every patient. An alternative method is to use scanner-independent dose conversion coefficients (DCCs) to estimate organ doses. DCCs, calculated by normalizing organ doses with respect to the corresponding CTDIvol, have been developed based on patient size, in terms of patient perimeter or effective diameter (ED) in the region of interest (ROI). However, patient dimensions do not take account of x-ray attenuation within the patient, which will affect the accuracy of dose assessment, as the attenuations of tissues are different for each patient. The aim of this study was to develop size-specific and scanner-independent DCCs by quantifying patient size in terms of water-equivalent diameter (Dw ). A library of 370 anatomical paediatric and adult phantoms was used. An algorithm was developed on MATLAB version 2015b to calculate Dw values for each phantom over six scan regions in the trunk. Organ doses and CTDIvol resulting from body scans acquired with 120 kVp were assessed using NCICT software for the phantom library to obtain DCCs. Good correlations were obtained between Dw as a measure for patient size and the DCCs, for which R 2 values of correlations were above 0.92 for the majority of organs. These could provide better assessments of organ doses than ones based on patient dimensions. Comparisons of lung doses from scans of different regions assessed using NCICT software and DCCs showed that values based on Dw values gave lower variations in dose by up to 12% compared to those based on ED. The correlations could potentially be utilized to assess organ doses for patients undergoing scans with any CT scanner. This would simplify organ dose estimation for patients and overcome the limitations associated with Monte Carlo simulations. Highlights: Dose conversion coefficients (DCCs) are used to estimate organ doses for CT patients. DCCs are established in terms of patient size, which is assessed from the patient dimensions. DCCs based on patient dimensions do not consider spectral attenuation of the scan region. Water-equivalent diameter (Dw) used for patient size can be applied for scanner–independent DCCs. Excellent correlations between Dw and DCC values for a range of organs were obtained.